Developing microsatellite markers for Cypripedium passerinum (Sparrow’s egg lady’s slipper) - Lim, Lina (My University, 2022)
Natural and anthropogenic disturbances contribute to increased habitat loss and fragmentation and subsequently, species loss. Integrated conservation approaches combine both in-situ and ex-situ approaches whereby natural habitats of endangered species are conserved, and the genetic diversity of the threatened population is retained outside of their natural habitat. Therefore, an essential component of an effective conservation strategy is to assess genetic variation to ensure that the conservation approach employed is effective in preserving the diversity of the whole population. Microsatellites, highly polymorphic repetitive DNA sequences in the genome of all organisms, have proven to be a valuable tool in the assessment of genetic diversity. This project aimed to isolate microsatellite markers from Cypripedium passerinum, a native North American terrestrial orchid at risk of extinction. Fast Isolation by AFLP of Sequences Containing Repeats (FIASCO) was employed to generate a genomic DNA library enriched for AT, AC, and AAG microsatellites. Clones were selected from the libraries and bidirectionally sequenced to identify those which contain microsatellites. A total of 158 microsatellite loci were identified, of which 83% were perfect microsatellites. PCR primers were developed using the unique sequences flanking the identified microsatellites and were evaluated for their utility. Primers amplifying polymorphic loci can be used to assess the genetic diversity of C. passerinum populations both within the Wagner Natural Area, Alberta, Canada and elsewhere in its range of distribution. The project findings will contribute to the integrated conservation efforts to protect species found in Wagner Natural Area and contribute to our understanding of C. passerinum.
Presented on: April 21, 2022 at Student Research Day at MacEwan University in Edmonton, Alberta; May 5-6, 2022 at the Undergraduate Research in Science Conference of Alberta held at MacEwan University in Edmonton, Alberta; March 10-11, 2022 at the Richard E. Peter Biology Conference at the University of Alberta, Edmonton, Alberta.
Keywords: conservation; microsatellites; genetic diversity; Cypripedium; FIASCO